2014
DOI: 10.1177/0363546514526549
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Injuries in Pole Vaulters: Response

Abstract: This letter is written in response to the article ''Catastrophic Injuries in Pole Vaulters: A Prospective 9-Year Follow-up Study'' by Boden et al. 1 The authors should be commended for their work in improving pole vault safety. However, I have some concerns. Based on a conclusion in the study that ''the average annual rate of catastrophic injuries from pole vaulters landing in the vault box has more than tripled over the past decade and remains a major problem,'' 1(p1488) the National Collegiate Athletic Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, 1 of the deaths, by account of the athlete's coach, was not the result of landing in the vault box area as suggested by Boden et al 1 The athlete landed on the runway or other surface in front of the pit. 5 Therefore, no deaths occurred during this time period by landing in the box. In addition, cross-referencing an 18-year-old high school female athlete's injury demonstrated that her injury occurred by hitting her head on the asphalt runway and not in the vault box area as noted by Boden et al 1 If both vault box landing injuries listed on the Pole Vault Power website (www.polevaultpower.com) were included in the NCCSIR data, then only 2 of 7 direct catastrophic injuries were the result of landing in the box or 28.6% (compared with 74% as reported by Boden et al 1 ).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, 1 of the deaths, by account of the athlete's coach, was not the result of landing in the vault box area as suggested by Boden et al 1 The athlete landed on the runway or other surface in front of the pit. 5 Therefore, no deaths occurred during this time period by landing in the box. In addition, cross-referencing an 18-year-old high school female athlete's injury demonstrated that her injury occurred by hitting her head on the asphalt runway and not in the vault box area as noted by Boden et al 1 If both vault box landing injuries listed on the Pole Vault Power website (www.polevaultpower.com) were included in the NCCSIR data, then only 2 of 7 direct catastrophic injuries were the result of landing in the box or 28.6% (compared with 74% as reported by Boden et al 1 ).…”
mentioning
confidence: 86%
“…This suggests that at most, the NCCSIR reported only 7 direct catastrophic injuries, which is in stark contrast to the 19 reported by Boden et al 1 One of the authors, Rebecca Peter, directed me to her website at www.polevaultpower.com, where she had listed 9 catastrophic cases during this time period of 2003-2011. 5 Reviewing these 9 cases, only 2 cases involved landing in the vault box area. All met the NCCSIR definition of a direct catastrophic injury.…”
mentioning
confidence: 99%
“…Interestingly, 1 of the deaths, by account of the athlete's coach, was not the result of landing in the vault box area as suggested by Boden et al 1 The athlete landed on the runway or other surface in front of the pit. 5 Therefore, no deaths occurred during this time period by landing in the box. In addition, cross-referencing an 18-year-old high school female athlete's injury demonstrated that her injury occurred by hitting her head on the asphalt runway and not in the vault box area as noted by Boden et al 1 If both vault box landing injuries listed on the Pole Vault Power website (www.polevaultpower.com) were included in the NCCSIR data, then only 2 of 7 direct catastrophic injuries were the result of landing in the box or 28.6% (compared with 74% as reported by Boden et al 1 ).…”
mentioning
confidence: 86%
“…This suggests that at most, the NCCSIR reported only 7 direct catastrophic injuries, which is in stark contrast to the 19 reported by Boden et al 1 One of the authors, Rebecca Peter, directed me to her website at www.polevaultpower.com, where she had listed 9 catastrophic cases during this time period of 2003-2011. 5 Reviewing these 9 cases, only 2 cases involved landing in the vault box area. All met the NCCSIR definition of a direct catastrophic injury.…”
mentioning
confidence: 99%